REDESIGN SIGN SYATEM PENANGKARAN PENYU DI PARIAMAN - MILA DARMAYATI, Hendra Afriwan, S.Sn., M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Sign system is a sign commonly used as a means to facilitate visitors to more easily interact with the environment. defines a directive, a command or a prohibition through symbols expressing the meaning of rules that are easily understood by the general public. A good sign system is a medium that can communicate focused information by considering alignment between color, letter, shape, size, layout and economically can save time and cost, and have a good level of legibility.The purpose of making this sign system is to improve the existing sign system to be more communicative in terms of font selection, color, layout, material sign system and also the location of placement sign system conservation area in helping facilitate visitors in the Pariaman Turtle Breeding when heading and being in Turtle Breeding area. The audiance target of this design is the Pariaman community, especially the junior and senior high school students. In addition to the background of more adolescent visitors who make educational visits, adolescents are also individuals who have good enough kongnitif skills so that delivery of messages will be more effective.This media sign system contains text and illustrations in the design. This design is made by using the theory of Visual Communication Design books, Layout, Illustration, and Typography. Method of data analysis performed is 5W + 1H obtained by interview data collection method, observation, and documentation.The main media in this design is supported by some supporting media such as: posters, pins, key chains, stickers, clothes, totebag, and notebook. In addition to supporting media, these media also serve as promotional media.